Roadmap on nanomedicine for the central nervous system. (14th February 2023) - Ciofani, Gianni; Campisi, Marco; Mattu, Clara; Kamm, Roger D; Chiono, Valeria; Raynold, Aji Alex Moothedathu; Freitas, João S; Redolfi Riva, Eugenio; Micera, Silvestro; Pucci, Carlotta; Novio, Fernando; Lorenzo, Julia; et al.
Abstract: In recent years, a great deal of effort has been undertaken with regards to treatment of pathologies at the level of the central nervous system (CNS). Here, the presence of the blood-brain barrier acts as an obstacle to the delivery of potentially effective drugs and makes accessibility to, and treatment of, the CNS one of the most significant challenges in medicine. In this Roadmap article, we present the status of the timeliest developments in the field, and identify the outstanding challenges and opportunities that exist. The format of the Roadmap, whereby experts in each discipline share their viewpoint and present their vision, reflects the dynamic and multidisciplinary nature of this research area, and is intended to generate dialogue and collaboration across traditional subject areas. It is stressed here that this article is not intended to act as a comprehensive review article, but rather an up-to-date and forward-looking summary of research methodologies pertaining to the treatment of pathologies at the level of the CNS.